Influence of protective structures on the development and productivity of tomatoes - Pastukhova, Anna; Petrov, Andrey; Makarova, Ksenia; Yakovlev, Matvey; Kolbina, Olga; Potapov, Pavel (Nexo Revista Científica, 2022)
The need to obtain consistently high yields of agricultural plants in the Siberian Federal District is sufficiently high. Therefore, this work aimed to study the influence of protective structures on the growth, development, and productivity of tomatoes in the Novosibirsk region. The data obtained allow concluding that the use of protective structures protects plants from recurrent frosts, gusts of northern winds, and a sharp drop in temperature. Plants grown in standard protective structures, in the first periods after planting at a permanent place of growth, were subjected to stressful situations, which led to a decrease in the immunity of the plant and, as a result, damage by fungi and bacteria.